Implementation of Discipline Values for the Learning Success of Upper Elementary School Students at MI Darul Hikmah Agung Jaya (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the implementation of discipline values and the obstacles faced at MI Darul Hikmah Agung Jaya. Using a descriptive qualitative approach, data were collected from teachers, students, and parents through interviews, observations, and documentation, then analyzed through data reduction, display, and conclusion drawing. Data validity was ensured by triangulation of techniques and sources. The findings show that teachers instill discipline values through two main techniques. First, external control, in which teachers give warnings, threats, or punishment to undisciplined students and provide rewards or praise to those who obey the rules. For example, students who consistently complete homework may receive additional grades or verbal appreciation. Second, teachers also become role models, demonstrating punctuality, neat appearance, polite language, and respectful attitudes, thereby fostering discipline by example. Furthermore, teachers apply cooperative control, emphasizing collaboration and agreements between teachers and students. This approach promotes tolerance, respect, and responsibility by involving students in creating and maintaining classroom rules. However, some obstacles were identified. Teachers were sometimes less assertive in enforcing discipline, and limited variation in teaching methods led to student boredom. In addition, inadequate attention, motivation, and parental support negatively influenced students’ discipline, resulting in lateness, incomplete assignments, and other undisciplined behaviors.